PENGARUH KOMITE AUDIT, CAPITAL INTENSITY RATIO, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia tahun 2016-2018) - Fitrianti Fatma; Andreas Andreas; Susilatri Susilatri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to examine effect of audit committee, capital intensity ratio, leverage, size of companies on tax avoidance in manufacturing companies that listed in the Indonesia Stock Exchange Period 2016-2018. The data used in this research a secondary data that obtained from company’s annual report and/or financial report. The number of samples 25 companies that are determined by purposive sampling method. The data analysis technique used in this research is descriptive statistical analysis of multiple linear regression analysis using Statistical Product and Service Solution (SPSS) version 22.0 for Windows as a data processing software program. The results of this study indicate the audit committee, leverage, and size of companies have significant effect on tax avoidance, while capital intensity ratio does not have significant effect on tax avoidance. Based on calculation of coefficient determination (R²) was 0,178. audit committee, capital intensity ratio, leverage, size of companies on tax avoidance simultaneously giving effect was 17,8%. While the remaining 82,2% influenced by other independent variables that are not observed in this research.Keywords : Audit Committee, Capital Intensity Ratio, Leverage, Size Of Companies, Tax Avoidance.